Meiotic Chromosome Synapsis and XY-Body Formation In Vitro - Lei, Qijing; Zhang, Eden; van Pelt, Ans M. M.; Hamer, Geert (Frontiers in Endocrinology, 2021)
To achieve spermatogenesis in vitro, one of the most challenging processes to mimic is meiosis. Meiotic problems, like incomplete synapsis of the homologous chromosomes, or impaired homologous recombination, can cause failure of crossover formation and subsequent chromosome nondisjunction, eventually leading to aneuploid sperm. These meiotic events are therefore strictly monitored by meiotic checkpoints that initiate apoptosis of aberrant spermatocytes and lead to spermatogenic arrest. However, we recently found that, in vitro derived meiotic cells proceeded to the first meiotic division (MI) stage, despite displaying incomplete chromosome synapsis, no discernible XY-body and lack of crossover formation. We therefore optimized our in vitro culture system of meiosis from male germline stem cells (mGSCs) in order to achieve full chromosome synapsis, XY-body formation and meiotic crossovers. In comparison to previous culture system, after meiotic initiation, the in vitro-generated spermatocytes were transferred to a freshly plated monolayer of proliferatively inactivated immortalized Sertoli cells supporting undifferentiated mGSCs to simulate the multiple layers of germ cell types as exist in vivo in the testis. We found that in this optimized culture system, although independent of the undifferentiated mGSCs, meiotic chromosome synapsis was complete and XY body appeared normal. However, meiotic recombination still occurred insufficiently and only few meiotic crossovers were formed, leading to MI-spermatocytes displaying univalent chromosomes (paired sister chromatids). Therefore, considering that meiotic checkpoints are not necessarily fully functional in vitro, meiotic crossover formation should be closely monitored when mimicking gametogenesis in vitro to prevent generation of aneuploid gametes.